Peran Direktorat Lalu Lintas Polda Sumatera Utara Dalam Menciptakan Akuntabilitas Pelayanan Publik - Muhammad Ikhwan; Alpi Sahari; Ahmad Fauzi (Mahesa Research Center, 2020)
Public demands for the creation of good governance especially in the public service sector which is based on good governance and clean govenance produce Polri institutions as sub-systems in the field of public services are required to be responsible in carrying out their duties in a professional and accountable manner. The National Police in particular carries out functions in the field of Registration and Identification of Motorized Vehicles (Regident Ranmor) who have strived to improve themselves by taking steps to reform the police that are moral, professional, modren, and independent through e-government systems in public services, this study aims to analyze the role of the North Sumatra Regional Police traffic directorate in creating public service accountability and efforts in creating public service accountability by the North Sumatra regional police traffic directorate. The results of this study indicate that the regent then is one of the functions of the police in the field of traffic which has the task of being one of the functions of the police in the field of traffic which provides services to the public in the field of motor vehicle administration services, namely issuance (SIM STNK, STCK, BPKB), material training (SIM, STNK, BPKB, TNKB). Public services in the field of registration and identification of motor vehicles carried out by the Directorate of Traffic of the North Sumatra Regional Police based on community satisfaction, it is expected that a survey of the community is carried out periodically (at least once a year) to find out the hopes, desires of the community for the services provided in order to provide excellent service to the community